PHYSICAL WATER QUALITY PARAMETERS IN BOYO RIVER ONOWAEMBO VILLAGE, GUNUNGSITOLI SUBDISTRICT, GUNUNGSITOLI CITY - Zega, Asokhiwa; Telaumbanua, Betzy Victor; Laoli, Destriman; Zebua, Ratna Dewi (Universitas Teuku Umar, 2023)
Water is a natural resource needed for many people’s livelihood. Clean water quality would affect the health of the environment and all activities beyond. This research was conducted on October 28th 2022 in Boyo River. The purpose of this study was to figure out the measurement of physical quality parameters and to determine the condition of Boyo River. Observations of physical water quality parameters were carried out at 3 location points through observation method. Data from measurements of current speed, depth, sunlight penetration, bottom substrate, river width, water color and odor were analyzed descriptively. The research result showed that the Boyo River in Onowaembo Village had not been polluted in accordance with PP No. 82 of 2001.